Trace Element Composition and Cathodoluminescence of Quartz in the Hongniu–Hongshan Skarn Deposit in Yunnan Province, Southwest China - Wang, Shi-ling; Peng, Hui-juan; Wang, Tian-rui; Zou, Hao; Zhou, Qi; Yang, Dong-jie; Sun, Ce; Tian, Xue (Frontiers in Earth Science, 2022)
The Hongniu–Hongshan Cu skarn deposit is located in the central part of the Zhongdian porphyry and skarn Cu belt in southwestern China. Various elements, including Al, Ti, Li, K, Na, Ca, Fe, and Ge, have been completed by using scanning electron microscopy–cathodoluminescence (SEM-CL) and laser ablation inductively coupled plasma-mass spectrometry (LA-ICP-MS) on quartz phenocrysts from the Hongniu–Hongshan porphyry and skarn Cu deposit. Three quartz generations were identified in the porphyritic granite based on the CL textures and trace element signatures. Samples of the first-generation quartz (Qtz1) contain dark gray luminescent cores assaying 22–85 ppm Ti, 58–129 ppm Al, 4–18 ppm Li, and 0.43–40 ppm Fe. The Ti-in quartz geothermometer indicates crystallization temperatures of 593–664°C for Qtz1. Samples of the second-generation quartz (Qtz2) are characterized by clear bright gray oscillatory overgrowths with medium Ti concentrations of 51–70 ppm with elevated and variable amounts of Al, Li, and Fe, and low K. The Ti-in quartz geothermometer indicates crystallization temperatures of 672–706°C. Samples of the third-generation quartz (Qtz3) contain narrow light gray rims assaying 56–93 ppm Ti, 80–101 ppm Al, 11–19 ppm Li, 1.42–17 ppm K, and 2–25 ppm Fe. The Qtz3 crystallised crystallized at higher temperatures of 706–799°C. Our study indicates that the quartz phenocryst in the Hongniu–Hongshan porphyry may have undergone two mixing episodes involving a second hotter magma. Before the first resorption, average Ti concentration in the quartz phenocryst cores was 24 ppm, and Ti of the bright band halo at the edge of the crystal core is 56 ppm; the maximum temperature difference is 109°C higher than that of the pre-resorption. Furthermore, the Ti concentration is 75 ppm at the edge of the quartz phenocryst before resorption. After resorption, the average Ti increased to 81 ppm at maximum temperature difference of 54°C higher than that of pre-resorption. Moreover, on the basis of quartz composition collected from 14 different deposits and our new dataset, we propose that covariations of Ge/Al ratio can be used to effectively discriminate magmatic quartz and hydrothermal quartz. Magmatic quartz has a Ge/Al ratio of <0.013, and the hydrothermal quartz has a ratio of >0.013.